The cooperation between suppliers and an agro-industrial slaughterhouse: a measurement tool - João Cuareli Alécio; Alvaro Neuenfeldt Júnior; Julio Siluk; Angélica Alebrant Mendes; Bruna Rigon de Oliveira; Mário Mello (Production)
Abstract Paper aims To identify factors to measure the cooperation between an agro-industrial pork slaughterhouse cooperative and input suppliers. Originality A performance measurement tool applicable in real-life industry practices related to input suppliers, based on critical success factors. Research method The performance measurement tool was calculated based on the analytic hierarchy process (AHP) procedure, constituted by two essential elements, the critical success factors and the key performance indicators, organized in a hierarchical structure. The key performance indicators are used to detail the critical success factors, measuring the supplier’s performance in relation to specific cooperation characteristics. Main findings In general, 77% of suppliers are fully or potentially cooperative with an established performance in risk sharing and information sharing factors. For the remaining 23% of suppliers classified as partially cooperatives, suggestions were proposed for changes to be implemented which improve their cooperation level performance. Finally, a direct relation between a low proportion of input discards and a established cooperative performance between suppliers and the analyzed agro-industrial pork cooperative was not verified. Implications for theory and practice To provide a performance measurement tool developed with methodological rigor to be used by researchers and agro-industrial pork slaughterhouse cooperative managers to improve the Brazilian pork slaughterhouse supply chain context.